Molecular Characterization of Exploitation of the Polyubiquitination and Farnesylation Machineries of Dictyostelium Discoideum by the AnkB F-Box Effector of Legionella Pneumophila - Abu Kwaik, Yousef; Al-Quadan, Tasneem (Frontiers in Microbiology, 2011)
The Dot/Icm-translocated Ankyrin B (AnkB) F-box effector of L. pneumophila is essential for intra-vacuolar proliferation and functions as a platform for the docking of polyubiquitinated proteins to the Legionella-containing vacuole (LCV) within macrophages and amoeba. Here we show that ectopically expressed AnkB in D. discoideum is targeted to the plasma membrane where it recruits polyubiquitinated proteins and it trans-rescues the intracellular growth defect of the ankB null mutant, which has never been demonstrated for any effector in amoeba. Using co-immunoprecipitation and Bimolecular Fluorescence Complementation (BiFC) we show specific interaction of Skp1 of D. discoideum with the F-box domain of AnkB, which has never been demonstrated in amoeba. We show that anchoring of AnkB to the cytosolic face of the LCV membrane in D. discoideum is mediated by the host farnesylation of the C-terminal eukaryotic CaaX motif of AnkB and is independent of the F-box and the two ANK domains, which has never been demonstrated in amoeba. Importantly, the three host farnesylation enzymes FTase, RCE-1, and IcmT of D. discoideum are recruited to the LCV in a Dot/Icm-dependent manner, which has never been demonstrated in amoeba. We conclude that the polyubiquitination and farnesylation enzymatic machineries of D. discoideum are recruited to the LCV in a Dot/Icm-dependent manner and the AnkB effector exploits the two evolutionarily conserved eukaryotic machineries to proliferate within amoeba, similar to mammalian cells. We propose that L. pneumophila has acquired ankB through inter-kingdom horizontal gene transfer from primitive eukaryotes, which facilitated proliferation of L. pneumophila within human cells and the emergence of Legionnaires’ disease.